MANAGEMENT OF ANXIETY AND DEPRESSION TREATMENT OF PRE-SURGERY PATIENTS AT Dr. SOEBANDI REGIONAL PUBLIC HOSPITAL JEMBER - Sudjiwanati, Sudjiwanati (Jurnal Aplikasi Manajemen, 2018)
Management of anxiety and depression treatment that can help the process of a patient while undergoing surgery. This study aims to determine the management treatment of the pre-surgery patient that is through psycho-education to be psychologically prepared for surgery. The study was conducted in patients who will have surgery in Dr. Soebandi Hospital Jember. The sample in this study was 50 people with different levels of education and data analysis using SPSS 20. Based on the results of calculations of the Anova test, it was known that the F count 0.322 > than F table 0.318 with a significance value > 0.05. The result of that calculation showed that there is no significant effect between the management of pre-surgery patients'treatment with the level of depression and anxiety. The result of correlation test showed that depression had a positive relationship with the level of knowledge which means that patients with higher levels of education have depression when they have surgery, but anxiety has a negative correlation value which means that the higher the education level, the lower the anxiety level.